A single-dose, randomized, open-labeled, parallel-group study comparing the pharmacokinetics, pharmacodynamics and safety of leuprolide acetate microspheres 3.75 mg and Enantone® 3.75 mg in healthy male subjects - Hu, Xingjiang; Zhang, Qiao; Zheng, Yunliang; Zhai, You; Xu, Nana; Zhao, Qingwei; Liu, Jian; Wan, Longyan; Luo, Jindan (Frontiers in Pharmacology, 2022)
Leuprolide acetate microspheres developed by Shanghai Livzon Pharmaceutical Co., Ltd. (T) have been marketed in China for more than 10 years, benefiting a large number of patients, and will continue to play an important role in China. However, as a generic drug, it is unclear whether there is a difference in efficacy between T and the original product Enantone® (R). This study compared the differences in efficacy and safety of two 1-month depot formulations in 48 healthy Chinese male subjects by comparing multiple pharmacokinetic (PK) and pharmacodynamic (PD) parameters. The main research indicators were the PK parameters of leuprolide (Cmax, AUC0-t, AUC0-D7, and AUCD7-t) and the PD parameters of testosterone (Emax, AUEC0-t, AUEC0-D7, and AUECD7-t) after 42 days of administration. The Cmax, AUC0-t, AUC0-D7 and AUCD7-t of leuprolide were slightly higher in the T group than in the R group with 90% confidence intervals (CIs) of 94.43–118.53%, 109.13–141.88%, 109.53–139.54%, and 105.17–145.74%, respectively. No significant differences in the PD parameters (Emax, AUEC0-t, AUEC0-D7, and AUECD7-t) existed between the T and R groups, and 90% CIs were 62.80–93.57%, 88.17–110.55, 95.72%–118.50%, and 79.77–105.63, respectively. At 672 h (D28), the castration rate of T was 91.30% (21/23) and that of R was 60.87% (14/23). The PK characteristics were consistent and the inhibitory effects on testosterone levels were similar in both T and R groups; further, clinical safety was observed for both T and R formulations, suggesting that these two products can replace each other in clinical practice.